(untitled) (Medicine Today, 2019)
Introduction: Skin disorders are common in elderly people. Systemic diseases promote the development of dermatological conditions. Various systemic diseases contribute to the presence of cutaneous disorders, indicating the possibility that a skin abnormality may sometimes be the first and only symptom of a much more serious medical problem. The aim of the study to determine the frequency of skin diseases in elderly patients. Materials & Methods: This was a cross-sectional study and non-probability convenient sampling technique was used. Patients were recruited from attending the Dermatology Out-patient Department of SZMCH during the study from January’2018 to July’2018. Patients included in the study having skin diseases aged between 60-80 years, including all those who were diabetic and hypertensive because diabetes and hypertension are the most common comorbid conditions among these elderly patients. Patients were included having skin diseases including pruritus, dermatitis, xerosis, eczema, psoriasis, scabies, bacterial infection, and fungal infections. Results: More than half (53.0%) patients belonged to age 71-80 years. Three fourth (75.0%) patients had pruritus followed by 37(37.0%) had dermatitis, 24(24.0%) had xerosis, 23(23.0%) had eczema and 12(12.0%) had bacterial infections. Pruritis, dermatitis, eczema and bacterial infections were statistically significant (p<0.05) among three groups. Conclusion: More than half of the patients belonged to age more than 70 years of age. Most common (three fourth) skin patients had pruritis, followed by more common skin patients were found dermatitis, xerosis, eczema and bacterial infection. Pruritis, dermatitis, eczema and bacterial infections were statistically significant in different age groups. Medicine Today 2019 Vol.31(2): 98-101